ANALISIS BETON KEROPOS PADA KOLOM STRUKTUR DENGAN METODE QUALITY CONTROL CIRCLE (QCC) - rohmad nuryanto; Suryo Handoyo; Kusdiman Joko Priyanto (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2023)
Quality is a key factor that brings success in construction, growth, and improvement. Quality is a basic factor in consumer decisions that shapes determining the desired products and services. One of the factors that influences product quality is the quality control method, which will be able to improve the quality of the company's output by reducing the level of defects. The Quality Control Circle (QCC) method is a method that can be used to reduce defects in a relatively short time, can be carried out, and is easily implemented in small teams so that it does not involve all personnel in an organization. Apart from this, QCC can also save costs by improving quality because of its small organizational structure. To be able to survive in the midst of intense competition and the growth of the construction industry, companies must have advantages that other companies do not have. The determining factor of competitiveness is to improve quality. This effort was made by the company by making continuous improvements with the aim of reducing the number of product defects. The author used the quality control cylinder method to reduce defects in structural column work at Gadjah Mada University's Smart Green and Learning Center (SGLC) building project. The focus was on analyzing concrete structural columns to reduce defects and achieve a cost efficiency of 82.87%. Improvements were made to elements of the structural column work method, reducing 80% of defects. The QCC method was used to prevent defects from recurring in the product.